Significantly improved energy storage performance of flexible PVDF-based nanocomposite by loading surface-hydroxylated BaZr0.2Ti0.8O3 nanofibers. Issue 11 (1st June 2022) - Wang, Yan; Wang, Hao; Xu, Ke; Wang, Boying; Wang, Feng; Li, Chaolong; Diao, Chunli; Huang, Houbing; Zheng, Haiwu
Abstract: Dielectric capacitors composed of high-breakdown strength ( E b ) polymer and large-dielectric constant ( ε r ) inorganic nanofillers are pivotal components that are extensively used in power electronics. Herein, novel nanocomposites with poly(vinylidene fluoride) (PVDF) as matrix and BaZr0.2 Ti0.8 O3 (BZT) nanofibers as fillers was fabricated. To strengthen the dispersion of the BZT nanofibers and improve the compatibility between the fibers and the matrix, the nanofibers were coated with polydopamine. The values of Young's modulus and DC resistivity of BZT/PVDF nanocomposites firstly increase and then reduce as the increase of volume percentage content of BZT nanofibers, from which the maximum values of Young's modulus and DC resistivity were obtained at 5 vol% of BZT nanofibers content. Phase-field simulation is used to show the electric field distribution for different volume fraction of BZT/PVDF nanocomposites. Both experimental and theoretical results corroborate that the rational addition of BZT nanofibers into the PVDF matrix can lead to an improvement of E b of the nanocomposites. Strikingly, the optimal discharged energy density ( U d ) of the BZT/PVDF composite is 13.0 J/cm 3 with 5 vol% BZT filler at 5219 kV/cm, quite larger than that of PVDF ( U d 6.6 J/cm 3 and E b 4447 kV/cm). Meanwhile, the sample exhibits an ultra-fast discharge time ( t 0.9 ) of 0.14 μs under load resistor of 2000 Ω. It provides a feasible avenue to obtain good U d of the nanocomposites under low filler loading, which will yield good application prospect to next generation of electrical mini capacitors.